Special exits a graphic memoir - Farmer, Joyce 1938- (Fantagraphics Books, 2010)
A graphic memoir chronicling the decline of the authors elderly parents health, their relationship with one another and with their daughter, and how they cope with the day-to-day fragility of the most taxing time of their lives